Shedding light on followers' innovation implementation behavior: the role of transformational leadership, commitment to change, and climate for initiative - Michaelis, Björn; Stegmaier, Ralf; Sonntag, Karlheinz (Journal of managerial psychology, 2010)
Purpose - The purpose of this paper is to provide a deeper understanding of how transformational leadership relates to followers' innovation implementation behavior, the psychological mechanisms of this relationship, and the role of individual perceptions of climate for initiative. Design/methodology/approach - Perceptual data were collected from 198 employees in lower and middle management positions of a multinational automotive corporation. Relationships were tested using hierarchical regression analysis. Findings - Results demonstrate that transformational leadership was strongly related to followers' innovation implementation behavior and that the nature of this relationship was moderated by followers' levels of perceived climate for initiative. Additionally, commitment to change fully mediated the relationship between transformational leadership and followers' innovation implementation behavior. Research limitations/implications - The paper is based on a cross‐sectional design. A causal interpretation requires studies with experimental or longitudinal designs. Practical implications - Companies should invest in transformational leadership training and in the selection of supervisors with this leadership style before initiating the implementation of innovations. Enhancing contextual factors, such as a perceived climate for initiative, should be promoted by integrating them into organizations' reward systems. Originality/value - The paper is one of the first to investigate the relationship between transformational leadership and followers' innovation implementation behavior. It specifies the organizational contexts under which transformational leadership is most likely related to innovation implementation behavior, and those in which such a relationship is unlikely to occur.
Gesehen am 21.04.2023